2017
DOI: 10.3382/ps/pex218
|View full text |Cite
|
Sign up to set email alerts
|

Sodium butyrate improved performance while modulating the cecal microbiota and regulating the expression of intestinal immune-related genes of broiler chickens

Abstract: This study evaluated the effect of sodium butyrate (SB) on performance, expression of immune-related genes in the cecal tonsils, and cecal microbiota of broiler chickens when dietary energy and amino acids concentrations were reduced. Day-old male Ross 708 broiler chicks were fed dietary treatments in a 3 × 2 factorial design (8 pens per treatment) with 3 dietary formulations (control diet; reduction of 2.3% of amino acids and 60 kcal/kg; and reduction of 4.6% of amino acids and 120 kcal/kg) with or without th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
76
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(88 citation statements)
references
References 81 publications
7
76
1
4
Order By: Relevance
“…To further investigate the mechanism underlying BLJ mitigating NE-induced gut injury, the cecal microbiota structure was analyzed via Illumina MiSeq sequencing. This study revealed no differences in α-diversity of the cecal microbiota between the four experimental groups, which was consistent with previous results [67]. In addition, principal component analysis showed that BLJ supplementation, NE challenge or both altered the β-diversity of the cecal microbiota, indicating that these treatments significantly affected the intestinal bacterial community profiles.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…To further investigate the mechanism underlying BLJ mitigating NE-induced gut injury, the cecal microbiota structure was analyzed via Illumina MiSeq sequencing. This study revealed no differences in α-diversity of the cecal microbiota between the four experimental groups, which was consistent with previous results [67]. In addition, principal component analysis showed that BLJ supplementation, NE challenge or both altered the β-diversity of the cecal microbiota, indicating that these treatments significantly affected the intestinal bacterial community profiles.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, principal component analysis showed that BLJ supplementation, NE challenge or both altered the β-diversity of the cecal microbiota, indicating that these treatments significantly affected the intestinal bacterial community profiles. However, NE challenge reduced the relative abundance of the phylum Firmicutes (67.65% vs. 82.27%) and increased the relative levels of Bacteroidetes compared with those of the unchallenged group, which helps explain the impaired BWG in the NE-infected birds, consistent with previous research [67]. We also found that the relative abundance of Firmicutes increased, while the relative abundance of Bacteroidetes decreased after BLJ treatment in unchallenged birds.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Odoribacter spp. decreases in cecal communities have been associated with butyric acid supplementation in chicken diets (Bortoluzzi et al, 2017). Together, these observations suggest that increases in abundance and/or activity of butyrate-producing taxa, such as Faecalibacterium and Butyricicoccus spp., may in fact dictate community dynamics and host-microbiome activities by generating fermentative metabolites and perhaps influence phenotypes later in life.…”
Section: Differentially Abundant Lineagesmentioning
confidence: 92%
“…Accumulating evidences suggest that the intestinal microbiota could affect the poultry production [3].…”
Section: Introductionmentioning
confidence: 99%